Dissection of gene loci underlying pasting temperature in cassava. Issue 4 (4th July 2018) - Srisawad, Nattaya; Worrapitirungsi, Wikanda; Sraphet, Supajit; Boonseng, Opas; Smith, Duncan R.; Triwitayakorn, Kanokporn
ABSTRACT: In this study, a fine genetic map within the quantitative trait loci (QTL) underlying pasting temperature (PT) of cassava ( Manihot esculenta Crantz) was constructed using newly developed simple sequence repeat (SSR) markers. The SSRs were designed on the basis of two scaffolds (S11341 and S4043) of the cassava genome, which covered previously identified QTL regions of the PT trait. A total of 55 and 61 SSR markers derived from S11341 and S4043, respectively, representing 0.29% of the cassava genome, were generated; of which 23 and 19 showed informative polymorphic patterns. Consequently, all identified informative polymorphic markers were used to genotype 200 F1 progeny plants. The genotypic data were then analyzed, and the results showed that 480 markers were distributed across 23 linkage groups (LGs) with total length of 1, 334 centimorgans (cM). An analysis of QTL underlying the PT trait revealed that marker EME81 on LG 1 had significant associations ( P  < 0.0001) in all environments evaluated. Four candidate genes were identified and selected for gene expression analysis in the parents, and among F1 lines with high and low PT values. Significant differences were observed in relative expression of carbohydrate phosphorylase ( CP ) and starch synthase II ( SSII ) between high and low PT in 6-month-old cassava. We found CP and SSII genes to potentially control the PT trait. In addition, the marker EME81 was found to be a promising marker for specific PT trait selection in cassava populations, which should facilitate marker-assisted selection for desired PT traits.